Searching for Performance Accountability in Higher Education: A Case Study - Chaudhary, Nathuram (KMC Journal, 2024)
Accountability is vital in ensuring universities to provide top-notch education to their stakeholders in higher education. Therefore, it is imperative to examine how universities can achieve intended performance accountability. The study analyzes the performance accountability of higher education, considering core, essential, and supporting components to meet stakeholder expectations. Based on the case study design, the data were collected through semi-structured interviews with stakeholders and secondary sources. The study sample was selected through the purposive sampling method, i.e., the University Authority, the Campus chief, three chairpersons of the subject committee, the president of the Professor Union Unit, the Coordinator of the Self-Evaluation Committee, and four faculties. After analyzing the data, it has been concluded that in order to achieve performance accountability in higher education, it is essential to manage the learning process effectively, have a strategic implementation plan, prioritize leadership, and adhere to accountability processes. These crucial elements are key to creating a successful learning environment, improving the quality of education, and ensuring accountability in the higher education sector. I claimed that the seed capital model is developed to enhance quality education by increasing higher education performance accountability. The study findings can help University officials and faculties improve education quality and policy formulation. Additionally, this study contributes to the existing literature on the institutional process and achieving accountability in all components of higher education.